Erythrocyte Partitioning Profile of Isosteviol in Human and Rat Blood - Ayorinde Adehin, PhD; Keai Sinn Tan, PhD; Wen Tan, PhD (Elsevier, 2019)
ABSTRACT: Background: Isosteviol is a synthetic derivative of steviol glycosides with promising pharmacological properties and might find future use as a cardioprotective agent. Objective: A simple LC-MS/MS technique was developed and validated for the bioanalysis of isosteviol in plasma and erythrocytes. This method was subsequently utilized for the in vitro assessment of isosteviol's partitioning into blood compartments of humans and rats. Methods: Fresh blood samples from healthy humans and Wistar rats were equilibrated with 1, 10, and 30 µM isosteviol at 37 °C in a shaking dry-bath. The levels of isosteviol in plasma and erythrocytes partitions were determined in these samples, after separation, at intervals over a 60-minute period. The data derived was used to estimate erythrocyte-to-plasma and blood-to-plasma coefficients. Results: Mean erythrocyte-to-plasma partition coefficients (SD) after 60 minutes of equilibration were observed to be 0.039 (0.002) and 0.040 (0.003) in humans and rats, respectively. Derived values for the blood-to-plasma ratio (SD) were 0.576 (0.001) in humans and 0.543 (0.007) in rats, whereas plasma component binding was estimated to be more than 96%. Conclusions: The findings suggest that isosteviol preferentially partitions into plasma compartments in humans and rats. The significance of this profile for the efficacy, tissue uptake, and retention of isosteviol will have to be further studied. Key words: Cardioprotective agent, Erythrocytes, Isosteviol, Neuroprotection, Partitioning ratio, Steviol glycosides